The development of Web Based Expert System of Citrus Pests and Disease Consultation Using Bayesian Network Method. - I Wayan Santika (Universitas Pendidikan Ganesha, 2012)
Citrus is a plant that is widely available in the highlands. Many types of citruspests and plant diseases will lead to the farmers need the right knowledge andinformation to save energy and make effective against diseases and pests that attackcitrus crops. Due to lack of information and agricultural experts orange then the solutionis an expert system that is able to provide information and solutions to farmers.The expert system of citrus pests, disease consultation are using bayesianmethods and web-based network, so that information can be easily obtained by thefarmers. Data were obtained from the experts in the field of agricultural lime and storedin the knowledge base. This knowledge base would be processed and counted usingbayesian methods for the network concluded as posibility of how big of a pest anddisease would occurs. The purpose of this research were (1) Designing Expert SystemConsultation Citrus Pest and Disease Using Bayesian Network Web-Based Methods. (2)Implementing Expert System Consultation Citrus Pest and Disease Using BayesianNetwork-Based Methods of test results Web. Based on expert consultation system ofcitrus pests and diseases using the web-based bayesian network could make the processof consultation and able to provide information to visitors.